Intratympanic aminoglycosides for Ménière’s disease - Webster, K; Galbraith, K; Lee, A; MacKeith, S; Burton, M (Wiley, 2023)
Background Ménière's disease is a condition that causes recurrent episodes of vertigo, associated with hearing loss and tinnitus. Aminoglycosides are sometimes administered directly into the middle ear to treat this condition. The aim of this treatment is to partially or completely destroy the balance function of the affected ear. The efficacy of this intervention in preventing vertigo attacks, and their associated symptoms, is currently unclear.